Exploring the determinants of exclusive breastfeeding among infants under six months in the Gambia using gambian demographic and health survey data of 2019-20 - Bewuketu Terefe; Kegnie Shitu (BMC, 2023)
Abstract Introduction For infants, no one is as nutritious as breastmilk for the rest of their lives. It is a great guarantee for their future health, especially if they can exclusively breastfeed for the next few months, from the moment they are born until the end of the fifth month. Although breastfeeding rates are very low, there is no data record about it in the Gambia. Objective This study aimed to assess the status of exclusive breastfeeding and its determinants among infants under six months of age in the Gambia. Methods It is a secondary data analysis using the 2019-20 Gambia demographic and health survey data. A total of 897 weighted mother-infant paired samples were included in the study. A logistic regression analysis method was employed to declare factors significantly associated with exclusive breastfeeding among infants under six months of age in Gambia. Variables with a p-value of 0.2 were entered into multiple logistic regression analysis, and after controlling other confounding factors, an adjusted odds ratio of 95% CI was applied to identify associated variables. Results Exclusive breastfeeding was found in 53.63% only among infants under six months of age. Being a rural resident (AOR = 2.14, 95% CI: 1.33, 3.41), reading a newspaper (AOR = 5.62, 95% CI: 1.32, 24.09), and being counseled on breastfeeding by a health professional (AOR = 1.36, 95% CI: 1.01, 1.82) are times more likely to practice exclusive breastfeeding, respectively. On the other hand, a child with a fever (AOR = 0.56, 95% CI: 0.37, 0.84), a child whose age is 2-3 months (AOR = 0.41, 95 CI: 0.28, 0.59), and a child whose age is 4-5 months (AOR = 0.11, 95% CI: 0.07, 0.16) is less likely to be fed exclusively than a 0-1-month-old child. Conclusion Exclusive breastfeeding remains among the public health challenges in the Gambia. Strengthening health professionals' counseling techniques on breastfeeding and infant illnesses, promoting the pros of breastfeeding, and designing timely policies and interventions are urgently needed in the country.